The Northern Navajo frontier, 1860-1900 expansion through adversity - McPherson, Robert S. (University of New Mexico Albuquerque, NM, 1988)
McPherson argues that, instead of being a downtrodden group of prisoners, defeated militarily in the 1860s and dependent on the U.S. government for protection and guidance in the 1870s and 80s, the Navajo nation was vigorously involved in defending and expanding the borders of their homelands. This was accomplished not through war nor as a concerted effort, but by an aggressive defensive policy built on individual action that varied with changing circumstances. Many Navajos never made the Long Walk to Bosque Redondo. Instead they eluded capture in northern and western hinterlands and thereby pushed out their frontier. This book focuses on the events and activities in one part of the Navajo borderlands-the northern frontier-where between 1860 and 1900 the Navajos were able to secure a large portion of land that is still part of the reservation. This expansion was achieved during a period when most Native Americans were losing their lands
58720
Keywords: History